ANGI-03 Functional roles of CD166/activated leukocyte cell adhesion molecule (CD166/ALCAM) for glioblastoma invasion. (28th November 2020) - Kijima, Noriyuki; Nakagawa, Tomoyoshi; Achiha, Takamune; Hirayama, Ryuichi; Kinoshita, Manabu; Kagawa, Naoki; Kishima, Haruhiko
Abstract: CD166/activated leukocyte cell adhesion molecule (CD166/ALCAM) is a transmembrane receptor, widely expressed in various tissues, and is involved in several functions such as cell adhesion, neurogenesis and angiogenesis. We have previously reported that CD166/ALCAM is expressed on glioblastoma progenitor cells and is involved in glioblastoma invasion. However, we only have analyzed the functional roles of ALCAM using glioblastoma cell lines, not using patient derived xenografts. In this study, we investigated the functional roles of CD166/ALCAM using patient derived xenografts. We established CD166/ALCAM knocked-down glioblastoma patient derived cell lines by shRNA. For in vitro analysis, we seeded control and CD166/ALCAM knocked-down glioblastoma cells on culture dishes and performed time lapse analysis to investigate cell motility. For in vivo analysis, we orthotopically injected control and CD166/ALCAM knocked-down glioblastoma cells into the immunodeficient mice. When the mice got sick due to the tumor, we dissected the mice and analyzed the difference in invasion by immunohistochemical analysis. We found that CD166/ALCAM knocked-down glioblastoma cells significantly decreased cell motility by time lapse analysis. In addition, CD166/ALCAM knocked-down glioblastoma cells suppressed cell invasion and leptomeningeal metastasis by immunohistochemical analysis from patient derived xenografts. Our results suggest that CD166/ALCAM is involved in glioblastoma invasion, thus future studies are necessary to investigate whether CD166/ALCAM could be a therapeutic target for glioblastoma.